2021
DOI: 10.3389/fcimb.2020.620801
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Secretion, Viability, and Real-Time Proliferation of Apical-Papilla Stem Cells Upon Exposure to Oral Bacteria

Abstract: The use of stem cells from the apical papilla (SCAPs) has been proposed as a means of promoting root maturation in permanent immature teeth, and plays a significant role in regenerative dental procedures. However, the role of SCAPs may be compromised by microenvironmental factors, such as hypoxic conditions and the presence of bacteria from infected dental root canals. We aim to investigate oral bacterial modulation of SCAP in terms of binding capacity using flow cytometry and imaging, real-time cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 52 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…In agreement with our previous findings [22] using a V-PLEX human biomarker multiplex assay, F. nucleatum, but not E. faecalis, induced cytokine production of the proinflammatory chemokines IL-8 and IL-10 in SCAP. In the current study, we showed that viable F. nucleatum upregulated the secretion of chemokines and cytokines such as GM-CSF, GROα, IL-6, IL-8, MCP-1, and VCAM-1, as detected by microarray and transcriptomics.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with our previous findings [22] using a V-PLEX human biomarker multiplex assay, F. nucleatum, but not E. faecalis, induced cytokine production of the proinflammatory chemokines IL-8 and IL-10 in SCAP. In the current study, we showed that viable F. nucleatum upregulated the secretion of chemokines and cytokines such as GM-CSF, GROα, IL-6, IL-8, MCP-1, and VCAM-1, as detected by microarray and transcriptomics.…”
Section: Discussionsupporting
confidence: 92%
“…This pathway leads to a decrease in the immune response [44]. The pathway is activated by a TGF-β cytokine that was not included in the set of 105 cytokines applied on the membrane, but its secretion was analyzed in an earlier study [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, IL-8 was released only in low levels by DPSC as well as SCAP under standard conditions; however, a considerable increase was observed during osteogenic differentiation, especially in SCAP. Interestingly, a recent study also measured high levels of proinflammatory cytokines such as IL-8 released by SCAP exposed to different anaerobic oral bacteria [ 46 ]. In general, IL-8 promotes osteoclastogenesis and is associated with bone resorption [ 47 ].…”
Section: Discussionmentioning
confidence: 99%